Literacy Corner Management as an Alternative and Innovative Reading Space to Foster Reading Interest in Grade IV Students - Pambudi, Titis Rio; Nisa, Choirun (Universitas Muhammadiyah Surakarta, 2025)
This study was motivated by the low reading interest among elementary school students, which calls for innovation in alternative reading spaces in the classroom environment. The purpose of this study was to describe literacy corner management as an innovative reading space in increasing the reading interest of fourth-grade students at SD Muhammadiyah Plus Malangjiwan. The research method used a descriptive qualitative approach with fourth grade teachers and students as subjects. Data were collected through observation, interviews, and documentation, then analyzed through reduction, data presentation, and conclusion drawing. The results showed that literacy corner management had been implemented effectively through structured stages of planning, implementation, and evaluation. Teacher support, active student participation, and innovations such as attractive room layout and the use of QR codes on books contributed to increasing students' reading motivation and learning independence. The implications of this study confirm that literacy corners can be a practical strategy for strengthening literacy culture in elementary schools.